A Suite-Of-Models Approach to Stress-Testing Financial Stability - Henrik Andersen; Tor Oddvar Berge; Eivind Bernhardsen; Kjersti-Gro Lindquist; Bjørn Helge Vatne (Norges Bank, 2008)
This paper presents a suite of models developed to stress-test financial stability. A macro model is linked to micro data-based models for households, firms and banks. The macro model includes credit- and consumer confidence-driven house prices and feed-back effects from credit and house prices to the real economy, i.e. a financial accelerator. The consumer confidence effect helps us mimic non-linearity in the housing market. We use the macro model to design stress scenarios, which are fed into the three micro models. The household and firm models enable us to analyse pockets of credit risk. The bank model sums it all up by providing estimates of bank profitability and capital adequacy.
hdl:11250/2507966
Keywords: 330